Cytotoxicity and fragmentation pattern of Datura metel L. leaves using ultra-performance liquid chromatography-mass spectroscopy - Mohammad Adam Mustapa, Muhammad Taupik, A. Muthi Andi Suryadi, Mahdalena Sy Pakaya, Julyanty Akuba, Endah Nurrowinta Djuwarno, Warsono El Kiyat (Journal of Applied Pharmaceutical Science, 2023)
This scientific investigation was conducted to evaluate the cytotoxicity and ascertain the pattern of fragmentation of Datura metel L. leaves using ultra-performance liquid chromatography-mass spectrometry. Phytochemical screening, isolation, and cytotoxic testing with the brine shrimp lethality test have been carried out on D. metel L. leaves extract. Preparative thin-layer chromatography with chloroform:n-hexane (1:1 v/v) eluent was used to carry out the compound isolation process. The octadecyl silica column was the stationary phase employed. The motion phase that was used was an isocratic elution system with a positive ion mode and acetonitrile:water (15:85 v/v) ratio. The retention time (tR) on the chromatogram was 3.20 minutes, and there was just one visible distinct peak. The results showed that the Datura leaves contain flavonoids, alkaloids, steroids, and saponins. The cytotoxic activity test showed a high cytotoxic potential of Datura leaf extract with an LC50 value of 46.1636 μg/ml. The result also showed that the isolate was a steroid that belongs to the Withanolide group, namely, Baimantuoluoline D. The isolate had a molecular weight of [M+] 504.0591 m/z with daughter fragments forming 477.2583 m/z [M+ ¬- CH3-OH] and 301.1780 [M+ ¬-C9H11O4]. There are more than 600 activities of the Withanolide group that have been documented. However, the activity showed that Withanolide isolated from it has anti-microbial, anti-inflammatory, and cytotoxic potential. The phytochemical screening results showed that the Datura leaves contained alkaloids, flavonoids, steroids, and saponins. It is intended that a pharmaceutical formulation including D. metel essential oil as the active component will be created for further research.
Keywords: Datura, Datura metel L., Withanolide, UPLC-MS